A CASE STUDY ON MANAGEMENT OF FROZEN SHOULDER BY AGNIKARMA - Namrata sojitra (International Journal of Applied Ayurved Research, 2017)
Frozen shoulder, also known as Periarthritis or Adhesive capsulitis causes a significant loss in range of motion typically occurs in cycle of 3 stages. It predominantly occurs in females in their fifties. In textual references of Ayurveda Frozen Shoulder is closely related to Avabahuka. In this condition, Vata is localized in the shoulder region, getting aggravated, dries up the bindings (ligaments) of the shoulders, constricts the siras present there and causes Avabahuka. Modern medicial science plays very less role in the management of Frozen Shoulder. In Ayurveda various para-surgical procedures were mentioned for diseases of Vata and Kapha, in which Agni karma is one of them, that has been recommended in various musculoskeletal disorders. Hence a case study was conducted to evaluate the effectiveness of Agnikarma in frozen shoulder.